2023
DOI: 10.1071/sh23107
|View full text |Cite
|
Sign up to set email alerts
|

Integrating testing for sexually transmissible infections into annual health assessments for Aboriginal and Torres Strait Islander young people: a cross-sectional analysis

Heather McCormack,
Handan Wand,
Christopher Bourne
et al.

Abstract: Background In the context of an expanding syphilis epidemic, we assessed the integration of sexually transmissible infection (STI) testing within annual health assessments for Aboriginal and Torres Strait Islander young people aged 16–29 years in Aboriginal Community Controlled Health Services between 2018 and 2020. Methods Using routinely collected electronic medical record data from a national sentinel surveillance system (ATLAS), we performed a cross-sectional analysis to calculate the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, the proportion of health assessments inclusive of a chlamydia test that had a concurrent syphilis test increased more substantially in the postintervention period for men than for women. Although other studies have instead found that the uptake of STI testing overall is higher in young Aboriginal women [1,17,[69][70][71][72][73], our previous work has identified gender parity in STI testing in the context of the health assessment [74]. One potential explanation for this identified in the qualitative data was the impact of standardization resulting in routine tests being offered during the health assessment that clinicians may have previously used their discretion to skip.…”
Section: Principal Findingsmentioning
confidence: 81%
“…In addition, the proportion of health assessments inclusive of a chlamydia test that had a concurrent syphilis test increased more substantially in the postintervention period for men than for women. Although other studies have instead found that the uptake of STI testing overall is higher in young Aboriginal women [1,17,[69][70][71][72][73], our previous work has identified gender parity in STI testing in the context of the health assessment [74]. One potential explanation for this identified in the qualitative data was the impact of standardization resulting in routine tests being offered during the health assessment that clinicians may have previously used their discretion to skip.…”
Section: Principal Findingsmentioning
confidence: 81%